Improved Field Emission Properties of Carbon Nanostructures by Laser Surface Engineering - Minh Nhat Dang; Minh Dang Nguyen; Nguyen Khac Hiep; Phan Ngoc Hong; In Hyung Baek; Nguyen Tuan Hong (Nanomaterials, 2020)
We herein present an alternative geometry of nanostructured carbon cathode capable of obtaining a low turn-on field, and both stable and high current densities. This cathode geometry consisted of a micro-hollow array on planar carbon nanostructures engineered by femtosecond laser. The micro-hollow geometry provides a larger edge area for achieving a lower turn-on field of 0.70 V/µm, a sustainable current of approximately 2 mA (about 112 mA/cm2) at an applied field of less than 2 V/µm. The electric field in the vicinity of the hollow array (rim edge) is enhanced due to the edge effect, that is key to improving field emission performance. The edge effect of the micro-hollow cathode is confirmed by numerical calculation. This new type of nanostructured carbon cathode geometry can be promisingly applied for high intensity and compact electron sources.